Telekonsultasi Dalam Rangka Pemutusan Rantai Penularan Covid-19 di Kota Bengkulu - Dessy Triana, M. Biomed; Hardiansyah Hardiansyah; Sri Yunita; Miftahul Haniyah; Enny Nugraheni Sulistiyorini; Riry Ambarsarie; Rizkianti Anggraini; Elvira Yunita; Mardhatillah Sariyanti (DHARMA RAFLESIA, 2021)
Coronavirus Disease-19 (Covid-19) is a disease that has become a global epidemic.  The World Health Organization (WHO) has declared Covid-19 a pandemic. Indonesia declared the status of the Covid-19 disease to be an Emergency Response. Supporting the social distancing, the right strategy is needed to continue implementing health services amid the Covid-19 pandemic. This activity aimed to provide knowledge related to Covid-19 to the community and health consultations and medical advice through applications (teleconsultation) to minimize patients queuing at Health Service Facilities directly. The activity partners were the Indonesian Medical Association (IDI) Bengkulu City Branch, Bengkulu City Health Office, and the Indonesian Red Crescent (BSMI) Bengkulu City Region. The method of this activity was to provide socialization, health consultation and medical advice through applications (teleconsultation) regarding the spread, transmission and prevention of Covid-19 from May 1 to August 31 2020. The number of participants was 41 people from Bengkulu City. The highest number of diseases consulted were acute respiratory infections (38.7%.) and Covid-19 independent protocol consultation (31.58%.) Teleconsultation can be continued and developed into a patentable application. Application development is indispensable in responding to the challenges of the health world in the digital era.